2019
DOI: 10.1007/s12640-019-0010-z
|View full text |Cite
|
Sign up to set email alerts
|

Local Gastrointestinal Injury Exacerbates Inflammation and Dopaminergic Cell Death in Parkinsonian Mice

Abstract: The cause of progressive degeneration in Parkinson's disease is not clear, although, in the last years, different studies have suggested that both brain and peripheral inflammation could play a key role in the progression of this disorder. In our study, we aimed to analyze the effect of an acute inflammation confined to the colon on dopaminergic neuronal death and glial response in mice intoxicated with MPTP. The results obtained show a very significant decrease of dopaminergic neurons in the SNpc as well as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 50 publications
1
5
0
Order By: Relevance
“…The obtained data reinforces the activation of microglial related-events together with the exacerbation of the dopaminergic neurodegeneration 7 . Together with these observations, in our previous study, we showed an exacerbation of the dopaminergic neuronal death and the glial activation both in the SNpc and striatum when combining MPTP and DSS intoxications 8 .…”
Section: Introductionsupporting
confidence: 85%
See 2 more Smart Citations
“…The obtained data reinforces the activation of microglial related-events together with the exacerbation of the dopaminergic neurodegeneration 7 . Together with these observations, in our previous study, we showed an exacerbation of the dopaminergic neuronal death and the glial activation both in the SNpc and striatum when combining MPTP and DSS intoxications 8 .…”
Section: Introductionsupporting
confidence: 85%
“…We aimed to elucidate in depth the molecular and cellular mechanisms triggered after a systemic insult in the striatum of mice untreated and treated with MPTP. The importance of specifically studying the effect of both toxins in the striatum is based on previous data obtained by immunohistochemical techniques in which we observed exacerbation of the inflammatory events when combining both toxins 8 . The results from this study provide novel information about the DEGs in the striatum of mice intoxicated only with DSS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, a few recent studies have reported that colitis is sufficient to induce alterations in the dopaminergic nigrostriatal pathway. A reduction in expression of tyrosine hydroxylase (TH), the rate limiting enzyme in dopamine synthesis, in the SN was observed in a study using acute DSS alone 100 ; however, DSS in conjunction with the neurotoxin MPTP, resulted in enhanced reduction of TH expression in the SN, as well as increases in Iba1+ cells and GFAP+ cells, suggestive of a degenerative phenotype with astrogliosis and increased microglial activation 100 . In a separate study examining different paradigms of DSS induction, it has been reported that an acute model is sufficient to increase nigral IL-1β, suggesting alterations in the inflammatory state of the SN, but insufficient to produce nigrostriatal degenerative phenotypes.…”
Section: Evidence Linking Colitis and Pd-associated Neuropathology In Animal Modelsmentioning
confidence: 99%
“…Differentially expressed genes within the MPTP+DSS show functional enrichment in inflammation and programmed cell death and both toxins have a significant synergistic negative effect. Similarly, another study using MPTP+DSS mice showed significant decrease of dopaminergic neurons and dopaminergic fibers, suggesting that intestinal inflammation is able to exacerbate death of dopaminergic neurons through inducing system inflammation [ 148 ].…”
Section: Intestinal Dysfunctions In Pdmentioning
confidence: 99%